PERAN TEMAN SEBAYA DALAM PEMBENTUKAN AKHLAK ANAK: Studi Di MTs Muhammadiyah Curup - Nila Pratiwi; Sugiatni Sugiatni; Asri Karolina (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2021)
This study sought to investigate a depiction of students’ parallel social engagement pattern in MTS Muhammadiyah of Curup, Bengkulu. In so doing, it dealt with whether their peers played a role in the formation of students’ morality. The foregoing question was answered through field research using a qualitative approach. The subjects as well as informants of this study were the principal, teachers, and students at MTs Muhammadiyah of Curup. Data collection techniques were observation and interviews, and then the data were analyzed using Miles’ et al approach, namely data reduction, data presentation, and conclusion drawing. This study concluded that the role of peers for the formation of students’ morality was seen in students’ tendency to choose their playmates at school. If they preferred good friends, then they would follow those friends’ behavior, and vice versa. Efforts made by the school to overcome students who were not morally good were in a way that teachers consolidate with counseling teachers, class teachers, and parents in order to work together to overcome this problem.Keywords: Students’ morality, Peers